Ecosystem of Social Entrepreneurship in Developing Countries: A Bibliometric and Network Analysis - Judijanto, Loso (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the worldwide intellectual framework of research on social entrepreneurship ecosystems in developing nations through a comprehensive bibliometric and network analysis of Scopus-indexed publications. By employing VOSviewer, the study systematically maps co-occurrence patterns, co-authorship structures, and cross-country collaboration networks to identify the principal research themes, influential authors, and collaborative dynamics that shape this scholarly domain. The results reveal that “social entrepreneurship” functions as the core thematic cluster, strongly interconnected with concepts such as social innovation, sustainable development, inclusive growth, and entrepreneurial ecosystems. These associations demonstrate how social entrepreneurship in developing countries is increasingly positioned as a multidimensional catalyst for socio-economic transformation. The network visualizations further highlight strong linkages between innovation-oriented studies and sustainability-driven research streams, underscoring the systemic and interdependent characteristics of social entrepreneurship. These connections suggest that researchers increasingly view entrepreneurial initiatives not only as economic activities but also as mechanisms for addressing societal challenges, empowering communities, and strengthening local resilience. Country-level analysis indicates that the United States and the United Kingdom remain predominant contributors, yet there is a notable surge in scholarly output from emerging economies across Asia, Africa, and Latin America, reflecting growing academic interest and practical relevance in these regions. Research deepens theoretical understanding of social entrepreneurship ecosystems while offering practical insights for policymakers, development agencies, and practitioners seeking to cultivate supportive environments for socially driven ventures.